(untitled) (Journal of Hama University, 2024)
This study aims to study the impact of monetary policy in a square such as the magic role in Syria, using the autoregressive (VAR) model, and the financial data and reports published by the Central Bureau of Statistics in Syria, and the publications of the Central Bank of Syria were relied on according to annual data, and then the analysis was conducted. This data was collected during the period ((2011-2021) using the statistical program (EVIEWS10). The results of the study showed that the optimal state of the four goals of the Kaldur magic square was not achieved in the Syrian economy, and this was shown by the narrowness in the area of ​​the Kaldur magic square, where a high inflation rate and a decrease in the rate of economic growth were observed during the study period, and that achieving them is very difficult due to the inconsistency of these Objectives: When an improvement occurs in some axes of the magic square, a deterioration appears in other axes in the same period, especially since the matter remains linked to the change in the international situation, the turmoil of the security and political conditions, and economic sanctions. It was also found that there is a statistically significant causal relationship between the growth rate of the real monetary mass and the rate of Inflation, and the existence of a causal relationship between the growth rate of the real money supply and the current account balance in the balance of payments.